2016
DOI: 10.1002/lary.26391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of polyp recurrence after endoscopic sinus surgery for chronic rhinosinusitis with nasal polyposis

Abstract: Objective Chronic rhinosinusitis with nasal polyposis (CRSwNP) is a disease process that is driven, in part, by intrinsic mucosal inflammation. Surgery plus continued medical therapy is commonly elected by medically recalcitrant, symptomatic patients. The objective was to evaluate the prevalence of nasal polyp recurrence up to 18-months after endoscopic sinus surgery (ESS) with congruent continuing medical management. Study Design Prospective, multi-center cohort of adult patients undergoing ESS for medicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
285
4
6

Year Published

2017
2017
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(309 citation statements)
references
References 29 publications
14
285
4
6
Order By: Relevance
“…68 Adult (≥18 years of age) study participants were prospectively sampled from heterogeneous patient populations referred to tertiary, academic practices in North America for recalcitrant symptoms of CRS between March, 2011 and June, 2015. Diagnoses were confirmed by fellowship trained rhinologists using guidelines currently defined by the American Academy of Otolaryngology.…”
Section: Methodsmentioning
confidence: 99%
“…68 Adult (≥18 years of age) study participants were prospectively sampled from heterogeneous patient populations referred to tertiary, academic practices in North America for recalcitrant symptoms of CRS between March, 2011 and June, 2015. Diagnoses were confirmed by fellowship trained rhinologists using guidelines currently defined by the American Academy of Otolaryngology.…”
Section: Methodsmentioning
confidence: 99%
“…In patients with CRS and concomitant nasal polyps (CRSwNP), functional endoscopic surgery (FESS) may reduce asthma symptoms [132], however polyps tend to relapse [133]. Nasal polyps in severe asthma are predominantly eosinophilic, and treatment with anti-IL5 may be a future treatment option [134].…”
Section: Management Of Severe Asthmamentioning
confidence: 99%
“…11 The author concluded that after endoscopic sinus surgery, recurrence of polyp was common among the patients. The authors found that the risk factors for recurrence of the polyp were previous history of surgery on polyps and worse preoperative polyposis severity.…”
Section: Discussionmentioning
confidence: 99%